Production and evaluation of chicken antibodies against a synthetic peptide from glial growth factor. - Felizzola, Ornella; Martínez, Juan Carlos; Zerpa, Noraida; Malavé, Caridad (Investigación Clínica, 2013)
Neuregulins (NRG) are proteins that belong to the family of epidermal growth factors. It is well established that these factors are essential for the development and maintenance of the nervous system. Due to the difficulty of purifying enough quantities of these factors and the lack of specificity from commercially available antibodies, the aim of this work was to produce antibodies against a synthetic peptide capable to detect and identify neuregulin GGF isoforms. To accomplish this goal, polyclonal antibodies were raised in hens against a synthetic peptide designed from the GGF1 extracellular sequence. The sequence analysis was made using different epitope-predicting programs. Our results showed that the peptide sequence selected was immunogenic because it was capable of inducing a specific type B immune response in the experimental animal model. These antibodies were also capable of recognizing a recombinant GGF protein and GGF isoforms present in different samples. Our results suggest that the development of immunoglobulin Y (IgY) using synthetic peptides represents, a valuable tool for neuroscience research.